Substrates, inducers, inhibitors and structure-activity relationships of human Cytochrome P450 2C9 and implications in drug development - Zhou, Shu-Feng; Zhou, Zhi-Wei; Yang, Li-Ping; Cai, Jian-Ping (Current medicinal chemistry, 2009)
Cytochrome P450 2C9 (CYP2C9) is one of the most abundant CYP enzymes in the human liver. CYP2C9 metabolizes more than 100 therapeutic drugs, including tolbutamide, glyburide, diclofenac, celecoxib, torasemide, phenytoin losartan, and S-warfarin). Some natural and herbal compounds are also metabolized by CYP2C9, probably leading to the formation of toxic metabolites. CYP2C9 also plays a role in the metabolism of several endogenous compounds such as steroids, melatonin, retinoids and arachidonic acid. Many CYP2C9 substrates are weak acids, but CYP2C9 also has the capacity to metabolise neutral, highly lipophilic compounds. A number of ligand-based and homology models of CYP2C9 have been reported and this has provided insights into the binding of ligands to the active site of CYP2C9. Data from the site-directed mutagenesis studies have revealed that a number of residues (e.g. Arg97, Phe110, Val113, Phe114, Arg144, Ser286, Asn289, Asp293 and Phe476) play an important role in ligand binding and determination of substrate specificity. The resolved crystal structures of CYP2C9 have confirmed the importance of these residues in substrate recognition and ligand orientation. CYP2C9 is activated by dapsone and its analogues and R-lansoprazole in a stereo-specific and substrate-dependent manner, probably through binding to the active site and inducing positive cooperativity. CYP2C9 is subject to induction by rifampin, phenobarbital, and dexamethasone, indicating the involvement of pregnane X receptor, constitutive androstane receptor and glucocorticoid receptor in the regulation of CYP2C9. A number of compounds have been found to inhibit CYP2C9 and this may provide an explanation for some clinically important drug interactions. Tienilic acid, suprofen and silybin are mechanism-based inhibitors of CYP2C9. Given the critical role of CYP2C9 in drug metabolism and the presence of polymorphisms, it is important to identify drug candidates as potential substrates, inducer or inhibitors of CYP2C9 in drug development and drug discovery scientists should develop drugs with minimal interactions with this enzyme. Further studies are warranted to explore the molecular determinants for ligand-CYP2C9 binding and the structure-activity relationships.